Implementasi Konvensi Hak Anak (KHA) dalam Putusan Ḥaḍānah di Pengadilan Agama Sleman - Fakhris Lutfi Rofiki (Rumah Jurnal Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2020)
The author is interested in the decision regarding Child Custody which originated from the existence of divorce, so that when the verdictregarding divorce occurred indirectly it would be a matter of ḥaḍānah.With the Convention on the Rights of the Child (CRC) in which there is aproblem of good principles for children, according to the authors it isinteresting to study, using the best interest of child theory, how later theimplementation of the Convention on Child Rights in a Child Custodydecision and how later the judge in considering a case ḥaḍānah will referto the principles of the CRC or not, besides using the Compilation ofIslamic Law and the Marriage Law etc. This is the qualitative researchbased on descriptive analytic. Research results that the application of theConvention on the Rights of the Child in the ḥaḍānah decision in theSleman Religious Court is inseparable from seeing the condition of thechild (whose willingness / comfort to live with, environment, education)all must see or refer to the child or the child's interests without exception.